Envisioning the Future with Aboriginal Breast Cancer Survivors - Thomas-MacLean, Roanne; Poudrier, Jennifer; Brooks, Carolyn (Atlantis, 2008)
Photovoice is a newly emerging participatory method of research. In this article, we discuss findings resulting from a photovoice project completed with young Aboriginal women who had experienced breast cancer. Three key interrelated themes linked to ethnicity, age, and identity, were particularly salient for the research participants. These are conceptualized as: (1) shame and silence; (2) resilience and strength; and (3) support.